Identifikasi Deformasi Tektonik Aktif Berdasarkan Ekstraksi Kelurusan Morfologi dan Seismisitas di Sukabumi, Jawa Barat - Mahbub, Rizqi Muhammad; Ragil, Candra (EKSPLORIUM, 2021)
The epicenter of the earthquake in Sukabumi has formed subsurface deformation which is now also recorded on the surface area. This is manifested through the geomorphology of the scarp and river lineaments. Extraction of lineaments produced by geological deformation can be used to identify its active tectonic deformation. The research objective is to determine the relationship between the active fault structure and the dominant direction of lineaments in the study area. The Edge Enhancing Filtering method is used to interpret lineaments manually and semi-automatically. The lineament geospatial data was extracted using the Sastratenaya formula to determine the chronology of the lineaments formed. The Sastratenaya formula results showed the lineaments recorded by DEM images data processing, the first segment direction is N315°E and the second is N10°E, both are interpreted as the result of fault reactivation. It can be interpreted that the Cimandiri Fault, which is an active fault that has an N88°E/85° rake 33° sinistral oblique-slip fault movement, affects the lineaments direction of two segments in the research area of Sukabumi, West Java.